"The Popular Entertainment Side of Broadcasting Should Receive Much More Attention": The BBC, Comedy, and Nation-Building at Home and Abroad. (December 2022) - Mills, Brett
This article outlines and examines the role comedy and entertainment have played at the BBC in constructing a sense of national identity both in the UK and overseas. It demonstrates the ways in which UK national identities are intertwined with ideas of a sense of humour, and the extent to which this is a performative act. Beginning with a historical approach, the article shows how the BBC, over time, has employed comedy as a way to evidence particularities of UK national identities, and the importance of the organisation in contributing to this.